Prevalence and factors associated with internet addiction among adolescents in urban public schools – A cross-sectional study from an internet de-addiction center in South India - Palanivelraja T; Kanimozhi P; Kumar P; Anurekha V; Rathinavel C; Madhubala V; Kumaravel KS; Sumithra K (Asian Journal of Medical Sciences, 2023)
Background: The Internet has become an integral and indispensable part of the life of every human being. Aims and Objectives: The aim of this study was to estimate the prevalence and the factors associated with internet addiction (IA) in adolescents in urban public schools in South India. Materials and Methods: This is a cross-sectional study done in one boy’s and one girl’s school, in an urban area and included all the children from 8th to 12th standards from January 2023 to March 2023. The study tool used was Chen’s IA scale (CIAS). Internet usage was broadly classified into three categories: 1: Social networking and gaming, such as Facebook, 2: Chat/messenger services such as WhatsApp, and 3: Streaming applications such as YouTube. Data were analyzed statistically using Statistical Package for the Social Studies Version 26.0. Results: On analysis of CIAS scores, the prevalence of IA was 7.95% (n=692). A significantly higher number of boys had IA than girls (P=0.008). On analysis of the body mass index, a significantly larger number of overweight participants were observed in adolescents with IA. There was no significant difference between the two groups regarding age (P=0.13) or socioeconomic class (P=0.66). Usage of social networking sites/gaming was associated with significantly higher CIAS scores (P=0.003). Although the usage of the internet for streaming and chatting purposes was common, they were not associated with higher scores. Conclusion: IA is taking on new dimensions and is seen across all socioeconomic classes. Periodic screening, adequate treatment, and follow-up are important in nurturing physical and mental health of adolescents.